TEKNIK PENILAIAN BERBASIS KOMPETENSI TERHADAP KARYAWAN - Denny Erica (Universitas Bina Sarana Informatika, 2009)
Company Or organization, will harvest result if employees conduct work effectively. In order to the employees give effective result, they need training. Not merely all ‘professional’ or all ‘coach of full time’ in concerned in course of this, but also the personnel manager, line manager, supervisor, and take of duty one who partake to participate effectively in that training.With system competency-based, employees exposed to by system of training and assessment which focused at performance actual. giving framework of theory to evaluate effectiveness of training and assessment of individual performance.Keywords : Organizational, effective Result, system competency-based